The effect of turbidity and prey fish density on consumption rates of piscivorous Eurasian perch Perca fluviatilis - Lene Jacobsen; Søren Berg; Henrik Baktoft; P. Anders Nilsson; Christian Skov (Journal of Limnology, 2014)
Predator-prey interaction strengths in variable environments constitute a fundamental link to the understanding of aquatic ecosystem responses to environmental change. The present study investigates the effects of visibility conditions and prey fish density on predation rates of visually oriented piscivorous Eurasian perch Perca fluviatilis L. This was done in outdoor mesocosm (16 m2) experiments with clear water and two levels of turbidity (25 and 105 NTU) and two prey fish densities [3.1 and 12.5 roach Rutilus rutilus (L.) individuals m–2]. Perch consumption rates were affected by visibility less than expected, while they were highly affected by increased prey fish density. Perch responded to high prey density in all visibility conditions, indicating that prey density is more crucial for consumption than visibility in turbid lakes.